Cross-sectional United Kingdom surveys demonstrate that owners and veterinary professionals differ in their perceptions of preventive and treatment healthcare needs in ageing dogs - Wallis, Lisa J.; Radford, Alan D.; Belshaw, Zoe; Jackson, Jodie; Kubinyi, Eniko; German, Alexander J.; Westgarth, Carri (Frontiers in Veterinary Science, 2024)
Perceptions of dog owners and veterinary professionals (surgeons/nurses) can influence the preventive healthcare and treatment provided to dogs, especially at the senior life-stage, when chronic diseases become more common. This study compared perceptions of healthcare of dogs as they age between dog owners and veterinary professionals. Data from two online surveys (owners: N=633, veterinary professionals: N=305) examined perceived need for veterinary visits and vaccinations. In addition, 48 clinical signs were rated on perceived prevalence (whether owners' dogs had experienced them) and how urgently they should seek veterinary advice. Groups were compared using descriptive statistics and chi-square. Owners most often believed a "healthy" senior dog (>7 years) should go to the vet once a year (47% owners vs. 25% veterinary professionals, P<0.001), compared with veterinary professionals every 6 months (39% vs. 73%). A minority (14%) of owners would just take the dog "if they got sick" but only 2% of veterinary professionals advised this, and 16% of owners of dogs of all ages had not had any contact with their veterinary practice in the previous year. Nearly all veterinary professionals (92%) believed that senior/geriatric dogs should receive yearly vaccinations. However, 28% of owners' dogs of all ages were not vaccinated in the previous year and, of these, 33% did not believe that older dogs need vaccinations. Only 10% of dogs considered 'old' by their owners had attended a senior wellness clinic or examination, despite 14% of practices offering them. The three most common clinical signs reported by owners were slowing down on walks (57%), dental tartar (53%) and being stiff on rising (50%). Owners perceived urgency to seek veterinary care was lower if they had experienced the clinical sign before. In the current study, dog owners and veterinary professionals differed in their opinions about the need for veterinary care, suggesting new educational initiatives, and more effective communication is required.